Multilayer polyimide film and metal-clad laminate
By introducing non-thermoplastic polyimide layers and thermoplastic polyimide layers with specific structures into multilayer polyimide films, the problem of reduced film strength caused by desizing is solved, and the durability and processing stability of the film are improved.
Patent Information
- Application Number
- CN202480022253.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-29
- Filing Date
- 2024-03-14
- Publication Date
- 2025-11-14
AI Technical Summary
In the prior art, the strength of multilayer polyimide films is easily reduced during the desizing process, leading to cracks and breaks in the film, especially in roll-to-roll production.
A non-thermoplastic polyimide layer containing tetracarboxylic acid dianhydride residues of a benzophenone backbone and diamine residues of a biphenyl backbone is used in combination with a thermoplastic polyimide layer. By adjusting the content of diamine residues and acid dianhydride residues, the entanglement and rigidity of the polyimide molecular chain are improved, thereby enhancing the film's resistance to desizing.
It effectively suppressed the reduction in film strength caused by degumming, improved the strain retention rate and tensile stress of multilayer polyimide films, ensured that the film did not deform at high temperatures, and reduced the occurrence of warping and cracking.
Smart Images

Figure CN120957870A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to multilayer polyimide films and metal-coated laminates. Background Technology
[0002] In recent years, with the expanding demand for electronic products such as smartphones, tablets, and laptops, the demand for flexible printed circuit boards (hereinafter, sometimes referred to as "FPCs") has been continuously growing. Among them, FPCs using multilayer polyimide films containing thermoplastic polyimide layers as adhesive layers are expected to see further demand growth due to their excellent heat resistance and flexibility. Furthermore, in recent years, the advancement of lightweighting, miniaturization, and thin-film technology in electronic devices has led to a strong demand for finer FPC wiring.
[0003] In the fabrication of micro-scale double-sided and multi-layer FPCs, metal-clad laminates, typically made by laminating metal foils such as copper foil to both sides of a polyimide film serving as the substrate, are commonly used. FPC manufacturing involves creating holes (hereinafter sometimes referred to as "through holes") initially used to establish interlayer connectivity. By plating the inner walls of these through holes, the two sides of the circuit board can be made conductive. As a through-hole forming process, there are through-hole methods that use drills or lasers to create through-holes in the metal foils and insulating layers (polyimide layers) on both sides, and blind hole methods that use lasers or similar methods to cut the metal foil and insulating layer on one side, leaving the metal foil on the other side intact. However, blind hole methods are frequently used, especially in micro-scale FPCs, to efficiently utilize the floor area.
[0004] Traditionally, in such through-hole forming processes, after the holes are created, a wet desmearing process (hereinafter sometimes abbreviated as "desmearing treatment") is performed on the laminated board under heating to clean the interior of the holes, the surface of the metal foil, or to remove resin residue. Polyimide is prone to hydrolysis under alkaline conditions; therefore, there is a tendency for the film strength to decrease due to the desmearing treatment. If the film strength decreases, defects such as cracks and breaks may sometimes occur in the polyimide film (i.e., the substrate of the FPC) after the desmearing treatment.
[0005] Furthermore, to improve productivity, FPC manufacturing processes are gradually shifting from the existing batch (non-continuous) to roll-to-roll (continuous) processes. While roll-to-roll processes offer the prospect of cost reduction, the increased processing time in some steps leads to an overall longer processing time, resulting in a tendency for greater thermal load on the substrate. Additionally, tension must be applied to the substrate during transport to prevent wrinkles, thus increasing the mechanical load on the substrate compared to batch processes. Consequently, the reduction in film strength caused by desizing is more pronounced in roll-to-roll processes.
[0006] Previously, methods have been reported that involve adding a heat treatment step between laser processing and descaling to remove residual stress generated during laser processing and suppress cracking (e.g., Patent Document 1). Additionally, methods have been reported that suppress cracking by controlling the aggregation structure of polyimide laminated films (e.g., Patent Document 2).
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 2012-186377
[0010] Patent Document 2: Japanese Patent Application Publication No. 2017-177604 Summary of the Invention
[0011] The problem the invention aims to solve
[0012] However, the technologies disclosed in Patent Documents 1 and 2 leave room for improvement in suppressing the reduction in film strength caused by degumming treatment.
[0013] The present invention was made in view of the above-mentioned problems, and its object is to provide a multilayer polyimide film that can suppress the reduction in film strength caused by desizing treatment and a metal-clad laminate using the same.
[0014] Solution for solving the problem
[0015] <Methods of the Invention>
[0016] The present invention includes the following methods.
[0017] [1] A multilayer polyimide film having a non-thermoplastic polyimide layer and a thermoplastic polyimide layer disposed on at least one side of the aforementioned non-thermoplastic polyimide layer.
[0018] The aforementioned non-thermoplastic polyimide layer contains a tetracarboxylic dianhydride residue comprising a benzophenone backbone as a tetracarboxylic dianhydride residue and a diamine residue comprising a biphenyl backbone as a diamine residue.
[0019] The aforementioned content of diamine residues containing the biphenyl backbone is 30 mol% or more and 100 mol% or less relative to all diamine residues constituting the aforementioned non-thermoplastic polyimide.
[0020] [2] According to the multilayer polyimide film described above [1], the content of the tetracarboxylic acid dianhydride residues containing the benzophenone backbone is more than 30 mol% and less than 100 mol% relative to all tetracarboxylic acid dianhydride residues constituting the aforementioned non-thermoplastic polyimide.
[0021] [3] According to the multilayer polyimide film described in [1] or [2] above, the strain retention rate of the aforementioned non-thermoplastic polyimide layer after desizing treatment at a treatment temperature of 70°C and a treatment time of 5 minutes is 80% or more.
[0022] [4] The multilayer polyimide film according to any one of [1] to [3] above, wherein the tensile stress of the aforementioned non-thermoplastic polyimide layer at 10% strain is 220 MPa or more.
[0023] [5] The multilayer polyimide film according to any one of [1] to [4] above, wherein the linear expansion coefficient of the aforementioned non-thermoplastic polyimide layer is 5.0 ppm / K or more and 19.0 ppm / K or less.
[0024] [6] A metal-clad laminate having a multilayer polyimide film and a metal layer as described in any one of [1] to [5] above, the metal layer being disposed on the main surface of at least one of the aforementioned thermoplastic polyimide layers of the multilayer polyimide film.
[0025] The effects of the invention
[0026] According to the present invention, a multilayer polyimide film capable of suppressing the reduction in film strength caused by desizing treatment and a metal-clad laminate using the same can be provided. Attached Figure Description
[0027] Figure 1 A cross-sectional view illustrating an example of the multilayer polyimide film involved in this invention.
[0028] Figure 2 A cross-sectional view illustrating an example of the metal-clad laminate according to the present invention. Detailed Implementation
[0029] The preferred embodiments of the present invention will be described in detail below, but the present invention is not limited thereto. Furthermore, all academic and patent documents described in this specification are incorporated herein by reference.
[0030] First, the terms used in this specification will be explained. “Structural unit” refers to a repeating unit that constitutes a polymer. “Polyimide” refers to a polymer that contains a structural unit represented by the following general formula (1) (hereinafter sometimes referred to as “structural unit (1)”).
[0031]
[0032] In general formula (1), X 1 X represents a tetracarboxylic dianhydride residue (derived from a tetravalent organic group of tetracarboxylic dianhydride).2 It represents a diamine residue (an organic group derived from the divalent form of a diamine).
[0033] The content of structural unit (1) relative to all structural units constituting polyimide is, for example, 50 mol% or more and 100 mol% or less, preferably 60 mol% or more and 100 mol% or less, more preferably 70 mol% or more and 100 mol% or less, further preferably 80 mol% or more and 100 mol% or less, more preferably 90 mol% or more and 100 mol% or less, and may also be 100 mol%.
[0034] "Polyamic acid" is a polymer containing the structural unit shown in the following general formula (2) (hereinafter sometimes referred to as "structural unit (2)").
[0035]
[0036] In general formula (2), A 1 Indicates a tetracarboxylic dianhydride residue (derived from a tetravalent organic group of tetracarboxylic dianhydride), A 2 It represents a diamine residue (an organic group derived from the divalent form of a diamine).
[0037] The content of structural unit (2) relative to all structural units constituting polyamic acid is, for example, 50 mol% or more and 100 mol% or less, preferably 60 mol% or more and 100 mol% or less, more preferably 70 mol% or more and 100 mol% or less, further preferably 80 mol% or more and 100 mol% or less, more preferably 90 mol% or more and 100 mol% or less, and may also be 100 mol%.
[0038] Polyimide is an imide derivative of polyamic acid. Therefore, when the content of structural unit (2) is 100 mol% relative to all structural units constituting polyamic acid, the polyimide, as an imide derivative of this polyamic acid, has A in general formula (2). 1 The residues shown are X in general formula (1) 1 And has A in general formula (2) 2 The residues shown are X in general formula (1) 2 .
[0039] The "coefficient of linear expansion" is, unless otherwise specified, the coefficient of linear expansion when the temperature rises from 50°C to 250°C. The method for determining the coefficient of linear expansion is the same as or based on the method described in the examples below.
[0040] "Non-thermoplastic polyimide" refers to polyimide that, when fixed in a film (17.0 μm thick) to a metal frame and heated at 450°C for 2 minutes, does not wrinkle or elongate, but maintains its film shape (flat film shape). "Thermoplastic polyimide" refers to polyimide that, when fixed in a film (17.0 μm thick) to a metal frame and heated at 450°C for 2 minutes, does not maintain its film shape. In this specification, the non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer is sometimes abbreviated as "non-thermoplastic polyimide." Conversely, the thermoplastic polyimide contained in the thermoplastic polyimide layer is sometimes abbreviated as "thermoplastic polyimide."
[0041] The "main face" of a layered material (more specifically, a non-thermoplastic polyimide layer, a thermoplastic polyimide layer, a multilayer polyimide film, etc.) refers to the face that is orthogonal to the thickness direction of the layered material.
[0042] The "benzophenone skeleton" refers to a skeleton with two benzene rings bonded together by carbonyl groups.
[0043] The "biphenyl skeleton" refers to a bicyclic skeleton in which two benzene rings are bonded together by a single bond. Therefore, diamine residues containing the biphenyl skeleton do not include diamine residues with fused rings, such as 9,9-bis(4-aminophenyl)fluorene residues.
[0044] "The physical properties of the non-thermoplastic polyimide layer (tensile modulus, tensile stress at 10% strain, slope of the plastic deformation zone, coefficient of linear expansion, strain retention rate, etc.)" are the physical properties of a non-thermoplastic polyimide film with the same composition and thickness as the non-thermoplastic polyimide layer. The method for determining the physical properties of the non-thermoplastic polyimide film is the same as or based on the method described in the examples below.
[0045] Hereinafter, the term "system" is sometimes added after the compound name to refer to the compound and its derivatives in a general sense. Additionally, when "system" is added after the compound name to indicate the name of a polymer, unless otherwise specified, it means that the repeating unit of the polymer originates from the compound or its derivatives. Furthermore, tetracarboxylic dianhydrides are sometimes written as "acid dianhydrides".
[0046] The ingredients and functional groups exemplified in this instruction manual may be used alone or in combination with two or more unless otherwise specified.
[0047] The accompanying drawings referenced in the following description schematically illustrate the constituent elements for ease of understanding. The size, number, and shape of the constituent elements shown may differ from the actual figures for ease of illustration. Furthermore, for ease of explanation, identical constituent parts in later drawings are sometimes labeled with the same symbols and their descriptions are omitted.
[0048] <First Embodiment: Multilayer Polyimide Film>
[0049] The multilayer polyimide film according to the first embodiment of the present invention is a laminate having a non-thermoplastic polyimide layer and a thermoplastic polyimide layer disposed on at least one side (one main side) of the non-thermoplastic polyimide layer. The non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer has tetracarboxylic dianhydride residues containing a benzophenone backbone as tetracarboxylic dianhydride residues and diamine residues containing a biphenyl backbone as diamine residues. Furthermore, in the first embodiment, the content of diamine residues containing a biphenyl backbone in the non-thermoplastic polyimide is 30 mol% or more and 100 mol% or less relative to all diamine residues constituting the non-thermoplastic polyimide.
[0050] Hereinafter, tetracarboxylic acid dianhydrides containing a benzophenone skeleton are sometimes referred to as "BENDA". In addition, diamines containing a biphenyl skeleton are sometimes referred to as "BPDI".
[0051] According to the multilayer polyimide film of the first embodiment, the reduction in film strength caused by desizing treatment can be suppressed. The reason is as follows.
[0052] In the multilayer polyimide film according to the first embodiment, the non-thermoplastic polyimide has BENDA residues and BPDI residues containing a backbone with high rotational freedom, thus promoting the winding of the polyimide molecular chains. On the other hand, polyimides with BENDA residues typically exhibit low elasticity and a high coefficient of linear expansion due to the aforementioned high rotational freedom. However, in the first embodiment, by incorporating BPDI residues with high linearity into the molecular chains, and ensuring that the content of these BPDI residues is 30 mol% or more and 100 mol% or less relative to all diamine residues constituting the non-thermoplastic polyimide, the winding of the polyimide molecular chains can be promoted, and the rigidity of the polyimide molecular chains can be ensured. Therefore, the multilayer polyimide film according to the first embodiment can maintain a high film strength (tensile modulus, tensile elongation, etc.) even after desizing treatment. Thus, according to the multilayer polyimide film according to the first embodiment, the reduction in film strength caused by desizing treatment can be suppressed.
[0053] In the first embodiment, in order to further suppress the reduction in film strength caused by the desizing process, the content of BPDI residues in the non-thermoplastic polyimide is preferably 30 mol% or more and 80 mol% or less relative to all diamine residues constituting the non-thermoplastic polyimide, more preferably 30 mol% or more and 70 mol% or less, even more preferably 30 mol% or more and 60 mol% or less, and even more preferably 30 mol% or more and 50 mol% or less.
[0054] In the first embodiment, in order to further suppress the reduction in film strength caused by the desizing process, the content of BENDA residues in the non-thermoplastic polyimide is preferably 30 mol% or more and 100 mol% or less relative to all tetracarboxylic acid dianhydride residues constituting the non-thermoplastic polyimide, more preferably 30 mol% or more and 70 mol% or less, and even more preferably 30 mol% or more and 50 mol% or less.
[0055] Hereinafter, the property that can suppress the reduction in film strength caused by desizing treatment is sometimes referred to as "desizing solution resistance". Desizing solution resistance can be expressed as the retention rate of the fracture strain of the film after desizing treatment relative to the fracture strain (strain at fracture) of the film before desizing treatment. Hereinafter, the retention rate of the fracture strain of the film after desizing treatment relative to the fracture strain of the film before desizing treatment is sometimes referred to as "strain retention rate". In order to obtain a multilayer polyimide film with excellent desizing solution resistance, the strain retention rate of the non-thermoplastic polyimide layer after desizing treatment at a treatment temperature of 70°C and a treatment time of 5 minutes is preferably 80% or more. It should be noted that when the desizing treatment method is to perform the swelling process, roughening process and neutralization process described later in sequence, the "treatment temperature" and "treatment time" of the above desizing treatment are respectively the "treatment temperature" and "treatment time" in the roughening process.
[0056] In the manufacturing process of the metal-clad laminate, to suppress film deformation, the tensile stress at 10% strain of the non-thermoplastic polyimide layer is preferably 220 MPa or more, more preferably 240 MPa or more. Furthermore, to reduce residual strain during the formation of the metal-clad laminate, the tensile stress at 10% strain of the non-thermoplastic polyimide layer is preferably 320 MPa or less, more preferably 310 MPa or less. Hereinafter, the tensile stress at 10% strain is sometimes referred to as "stress at 10% strain". The stress at 10% strain can be adjusted, for example, by changing the content of residues derived from monomers with rigid structures (more specifically, BPDI residues, etc.).
[0057] For non-thermoplastic polyimide layers, the slope of the plastic deformation region in the stress-strain curve is preferably 2.0 or higher. Non-thermoplastic polyimide layers exhibit high durability against fracture in alkaline environments when they are less prone to plastic deformation and possess high yield strength. The plastic deformation region refers to the area of strain following the yield point in the stress-strain curve of a polyimide film during a tensile test. The characteristic of "less prone to plastic deformation" means that stress increases significantly in the plastic deformation region, or that the stress required for plastic deformation is high. The characteristic of "less prone to plastic deformation" is, for example, indicated by the slope of the plastic deformation region. The slope of the plastic deformation region is, for example, the slope of the SS curve in the plastic deformation region of a graph with the vertical axis representing "stress (MPa)" and the horizontal axis representing "strain (mm)" based on tensile properties determined according to ASTM D882. The slope of the SS curve in the plastic deformation region can be calculated using the following formula. It should be noted that in the following formulas, stress1 is the stress at 10% strain, stress2 is the fracture stress, strain1 is the strain at 10% strain, and strain2 is the fracture strain.
[0058] The slope of the ss curve in the plastic deformation region = (stress2 - stress1) / (strain2 - strain1)
[0059] The slope of the plastic deformation region of the non-thermoplastic polyimide layer is preferably 2.0 or higher, more preferably 2.2 or higher. When the slope of the plastic deformation region is 2.0 or higher, a highly aggregated structure with a high degree of polymer chain stacking is formed, and breakage can be suppressed during continuous FPC processing. While a high slope of the plastic deformation region is preferable, in order to suppress the occurrence of springback and the like, the slope of the plastic deformation region is preferably 4.5 or lower, more preferably 4.0 or lower.
[0060] The coefficient of linear expansion of the non-thermoplastic polyimide layer is preferably 5.0 ppm / K or higher and 19.0 ppm / K or lower, more preferably 6.0 ppm / K or higher and 15.0 ppm / K or lower, and even more preferably 7.0 ppm / K or higher and 12.0 ppm / K or lower. If the coefficient of linear expansion of the non-thermoplastic polyimide layer is 5.0 ppm / K or higher and 19.0 ppm / K or lower, the coefficient of linear expansion of the multilayer polyimide film can be adjusted to, for example, 14.0 ppm / K or higher and 22.0 ppm / K or lower, close to that of the copper foil, and ideally adjusted to 16.0 ppm / K or higher and 20.0 ppm / K or lower, even closer to that of the copper foil. This reduces the difference in thermal expansion between the copper foil and the film when the copper foil and the multilayer polyimide film are bonded at high temperatures. As a result, dimensional changes in the obtained copper-clad laminate (FCCL) can be suppressed. The aforementioned coefficient of linear expansion can be adjusted, for example, by changing the content of residues derived from monomers with rigid structures (more specifically, BPDI residues, etc.) and the content of residues derived from monomers with curved structures (more specifically, BENDA residues, etc.).
[0061] [Composition of multilayer polyimide films]
[0062] Next, the structure of the multilayer polyimide film according to the first embodiment will be described with reference to the accompanying drawings.
[0063] Figure 1 This is a cross-sectional view illustrating an example of the multilayer polyimide film according to the first embodiment. Figure 1 As shown, the multilayer polyimide film 10 has a non-thermoplastic polyimide layer 11 and a thermoplastic polyimide layer 12 disposed on at least one side of the non-thermoplastic polyimide layer 11. The non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer 11 has BENDA residues as tetracarboxylic dianhydride residues and BPDI residues as diamine residues. In addition, in the multilayer polyimide film 10, the content of BPDI residues in the non-thermoplastic polyimide is 30 mol% or more and 100 mol% or less relative to all diamine residues constituting the non-thermoplastic polyimide.
[0064] It should be noted that, Figure 1In the multilayer polyimide film 10 shown, a thermoplastic polyimide layer 12 is provided only on one side of the non-thermoplastic polyimide layer 11. However, thermoplastic polyimide layers 12 can also be provided on both sides (two main sides) of the non-thermoplastic polyimide layer 11. When thermoplastic polyimide layers 12 are provided on both sides of the non-thermoplastic polyimide layer 11, the two thermoplastic polyimide layers 12 can contain the same type of thermoplastic polyimide or contain different types of thermoplastic polyimide. Furthermore, the thicknesses of the two thermoplastic polyimide layers 12 can be the same or different. Additionally, in this invention, two or more non-thermoplastic polyimide layers 11 and thermoplastic polyimide layers 12 can be provided. In the following description, "multilayer polyimide film 10" includes: a film having a thermoplastic polyimide layer 12 on only one side of the non-thermoplastic polyimide layer 11; a film having a thermoplastic polyimide layer 12 on both sides of the non-thermoplastic polyimide layer 11; and a film having two or more layers of both non-thermoplastic polyimide layer 11 and thermoplastic polyimide layer 12.
[0065] The thickness of the multilayer polyimide film 10 (total thickness of all layers) is, for example, 6 μm or more and 60 μm or less. The thinner the multilayer polyimide film 10, the easier it is to achieve lightweighting of the resulting FPC, and the better the flexibility of the resulting FPC. To ensure mechanical strength while facilitating lightweighting and further improving the flexibility of the FPC, the thickness of the multilayer polyimide film 10 is preferably 7 μm or more and 30 μm or less, more preferably 10 μm or more and 25 μm or less. The thickness of the multilayer polyimide film 10 can be measured using a laser holographic length gauge.
[0066] To ensure good adhesion between the main surface 12a of the thermoplastic polyimide layer 12 and the metal foil, and to facilitate the thinning of the FPC, the thickness of the thermoplastic polyimide layer 12 (the thickness of each thermoplastic polyimide layer 12 if two or more layers are provided) is preferably 1 μm or more and 15 μm or less. Furthermore, to facilitate adjustment of the coefficient of linear expansion of the multilayer polyimide film 10, the thickness ratio of the non-thermoplastic polyimide layer 11 to the thermoplastic polyimide layer 12 (thickness of non-thermoplastic polyimide layer 11 / thickness of thermoplastic polyimide layer 12) is preferably 55 / 45 or more and 95 / 5 or less. When at least one of the non-thermoplastic polyimide layer 11 and the thermoplastic polyimide layer 12 is provided in multiple layers, the thickness used to calculate the above thickness ratio is the total thickness. Even if the number of thermoplastic polyimide layers 12 increases, it is preferable that the total thickness of the thermoplastic polyimide layers 12 does not exceed the total thickness of the non-thermoplastic polyimide layers 11.
[0067] To suppress warping of the multilayer polyimide film 10, it is preferable to provide thermoplastic polyimide layers 12 on both sides of the non-thermoplastic polyimide layer 11, and more preferably, thermoplastic polyimide layers 12 containing the same type of thermoplastic polyimide are provided on both sides of the non-thermoplastic polyimide layer 11. When thermoplastic polyimide layers 12 are provided on both sides of the non-thermoplastic polyimide layer 11, it is preferable that the thicknesses of the two thermoplastic polyimide layers 12 are the same to suppress warping of the multilayer polyimide film 10. It should be noted that even if the thicknesses of the two thermoplastic polyimide layers 12 are different, if the thickness of the other thermoplastic polyimide layer 12 is 40% or more but less than 100% when the thickness of the relatively thicker thermoplastic polyimide layer 12 is used as a reference, warping of the multilayer polyimide film 10 can be suppressed.
[0068] [Elements of Multilayer Polyimide Films]
[0069] Next, the elements (constituent elements) of the multilayer polyimide film according to the first embodiment will be described in detail.
[0070] (Non-thermoplastic polyimide layer)
[0071] The non-thermoplastic polyimide layer contains a BPDI residue as a diamine residue. Examples of diamines (monomers) used to form the BPDI residue include 4,4'-diamino-2,2'-dimethylbiphenyl (hereinafter, sometimes referred to as "m-TB"), 4,4'-diaminobiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-2,2'-dimethoxybiphenyl, 4,4'-diamino-3,3'-dimethoxybiphenyl, 3,3',5,5'-tetramethylbenzidine, and 4,4'-bis(4-aminophenoxy)biphenyl. In this embodiment, one or more diamines can be used as diamines used to form the BPDI residue. To further suppress the decrease in film strength caused by the desizing process, m-TB is preferred as the diamine (monomer) used to form the BPDI residue. That is, m-TB residues are preferred as BPDI residues.
[0072] Non-thermoplastic polyimides may also have diamine residues other than BPDI residues (other diamine residues) as diamine residues. As the diamine (monomer) used to form other diamine residues, aromatic diamines with high heat resistance are preferred. Specific examples of diamines used to form other diamine residues include p-phenylenediamine (hereinafter, sometimes referred to as "PDA"), 4,4'-diaminodiphenyl ether (hereinafter, sometimes referred to as "ODA"), 2,2-bis[4-(4-aminophenoxy)phenyl]propane (hereinafter, sometimes referred to as "BAPP"), 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-diaminodiphenylpropane, 4,4'-diaminodiphenylmethane, and 4,4'-diaminodiphenylmethane. Diphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,5-diaminonaphthalene, 4,4'-diaminodiphenyldiethylsilane, 4,4'-diaminodiphenylsilane, 4,4'-diaminodiphenylethylphosphine oxide, 4,4'-diaminodiphenylN-methylamine, 4,4'-diaminodiphenylN-phenylamine, 1,3-diaminobenzene, 1,2-diaminobenzene and their derivatives, etc.
[0073] As other diamine residues, a combination of one or more diamine residues with a flexible structure selected from the group consisting of ODA residues, BAPP residues, 1,3-diaminobenzene residues and 1,3-bis(4-aminophenoxy)benzene residues and PDA residues with a rigid structure is preferred, and a combination of ODA residues and PDA residues is even more preferred.
[0074] The content of other diamine residues is 0 mol% or more and 70 mol% or less relative to all diamine residues constituting the non-thermoplastic polyimide. Regarding the content of diamine residues with rigid structures among the other diamine residues, from the viewpoint of ensuring high heat resistance, it is preferably 10 mol% or more and 50 mol% or less relative to all diamine residues constituting the non-thermoplastic polyimide, more preferably 15 mol% or more and 40 mol% or less, and even more preferably 15 mol% or more and 35 mol% or less. Furthermore, in order to adjust the coefficient of linear expansion of the multilayer polyimide film to an appropriate range, the content of diamine residues with flexible structures among the other diamine residues is preferably 20 mol% or more and 60 mol% or less relative to all diamine residues constituting the non-thermoplastic polyimide, more preferably 25 mol% or more and 55 mol% or less, and even more preferably 30 mol% or more and 50 mol% or less.
[0075] The non-thermoplastic polyimide layer contains a BENDA residue as an acid dianhydride residue. Examples of acid dianhydrides (monomers) used to form the BENDA residue include 3,3',4,4'-benzophenone tetracarboxylic dianhydride (hereinafter sometimes referred to as "BTDA"), 2,2',3,3'-benzophenone tetracarboxylic dianhydride, and 2,3,3',4'-benzophenone tetracarboxylic dianhydride. In this embodiment, one or more acid dianhydrides can be used as the acid dianhydride used to form the BENDA residue. To further suppress the decrease in film strength caused by the desizing process, BTDA is preferred as the acid dianhydride (monomer) used to form the BENDA residue. That is, BTDA residues are preferred as the BENDA residue.
[0076] Non-thermoplastic polyimides can also have dianhydride residues other than BENDA residues (other dianhydride residues) as dianhydride residues. Examples of dianhydrides (monomers) used to form other dianhydride residues include, for example, pyromellitic dianhydride (hereinafter, sometimes referred to as "PMDA"), 3,3',4,4'-biphenyltetracarboxylic acid dianhydride (hereinafter, sometimes referred to as "BPDA"), 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 1,2,5,6-naphthalenetetracarboxylic acid dianhydride, 2,2',3,3'-biphenyltetracarboxylic acid dianhydride, and 4,4'-oxophthalic anhydride (hereinafter, sometimes referred to as...). ODPA, 3,4'-oxobis(phthalic anhydride), 2,2-bis(3,4-dicarboxyphenyl)malonide, 3,4,9,10-perylenetetracarboxylic anhydride, 1,1-bis(2,3-dicarboxyphenyl)oxalic anhydride, 1,1-bis(3,4-dicarboxyphenyl)oxalic anhydride, p-phenylenebis(triphenyltriglyceride monoester anhydride), ethylenebis(triphenyltriglyceride monoester anhydride), bisphenol Abis(triphenyltriglyceride monoester anhydride) and their derivatives, etc.
[0077] As for the other acid dianhydride residues, from the viewpoint of ensuring high heat resistance and low thermal expansion, it is preferable to select one or more from the group consisting of PMDA residues, BPDA residues, and ODPA residues; more preferably, it is preferable to select one or more from the group consisting of PMDA residues and BPDA residues; and even more preferably, it is preferable to select PMDA residues. From the viewpoint of ensuring high heat resistance and low thermal expansion, the content of the other acid dianhydride residues relative to all acid dianhydride residues constituting the non-thermoplastic polyimide is preferably 70 mol% or less, more preferably 10 mol% or more and 70 mol% or less, even more preferably 30 mol% or more and 70 mol% or less, and even more preferably 50 mol% or more and 70 mol% or less.
[0078] To maintain a good surface appearance of the metal-clad laminate and suppress the occurrence of film cracking and breakage during the FPC manufacturing process, the non-thermoplastic polyimide preferably has segments with repeating structural units as shown in the following chemical formula (3). It should be noted that, in this specification, "segment" refers to a polymer chain consisting of identical repeating units constituting a block copolymer. Furthermore, in this specification, "block copolymer" also includes any of the following: pure block copolymers, random block copolymers, and copolymers with a conical block structure.
[0079]
[0080] Segments of which the structural unit shown in chemical formula (3) is the repeating unit (hereinafter sometimes referred to as "specific segments") can be formed, for example, by sequential polymerization as described later.
[0081] The non-thermoplastic polyimide layer may also contain components other than non-thermoplastic polyimide (additives). Examples of additives include dyes, surfactants, leveling agents, plasticizers, silicones, fillers, and sensitizers. The content of non-thermoplastic polyimide in the non-thermoplastic polyimide layer relative to the total amount of the non-thermoplastic polyimide layer is, for example, 70% by weight or more, preferably 80% by weight or more, more preferably 90% by weight or more, and may also be 100% by weight.
[0082] (Thermoplastic polyimide layer)
[0083] The thermoplastic polyimide layer contains thermoplastic dianhydride residues and diamine residues. Examples of compounds that are the same as those used to form the dianhydride residues in non-thermoplastic polyimides can be cited as the dianhydride (monomer) used to form the dianhydride residues in thermoplastic polyimides. The dianhydride residues in thermoplastic polyimides and non-thermoplastic polyimides can be the same type or different types.
[0084] To ensure thermoplasticity, diamine residues having a curved structure are preferred as diamine residues in the thermoplastic polyimide. To more easily ensure thermoplasticity, the content of diamine residues having a curved structure relative to all diamine residues constituting the thermoplastic polyimide is preferably 50 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, and may also be 100 mol%. Examples of diamines (monomers) used to form diamine residues having a curved structure include 4,4'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, BAPP, etc. To more easily ensure thermoplasticity, BAPP residues are preferred as diamine residues in the thermoplastic polyimide.
[0085] To obtain a thermoplastic polyimide layer with excellent adhesion to the metal foil, the thermoplastic polyimide preferably has one or more residues selected from the group consisting of BPDA residues and PMDA residues, and also has BAPP residues. Furthermore, to further suppress the decrease in film strength caused by the desizing process, the total content of BPDA residues and PMDA residues relative to all dianhydride residues constituting the thermoplastic polyimide is preferably 85 mol% or more and 100 mol% or less, more preferably more than 85 mol% and 100 mol% or less, further preferably 90 mol% or more and 100 mol% or less, more preferably 95 mol% or more and 100 mol% or less, and particularly preferably 100 mol%.
[0086] The thermoplastic polyimide layer may also contain components other than thermoplastic polyimide (additives). Examples of additives include dyes, surfactants, leveling agents, plasticizers, silicones, fillers, sensitizers, etc. The content of thermoplastic polyimide in the thermoplastic polyimide layer relative to the total amount of the thermoplastic polyimide layer is, for example, 70% by weight or more, preferably 80% by weight or more, more preferably 90% by weight or more, and may also be 100% by weight.
[0087] [Preferred embodiment of the first implementation]
[0088] To further suppress the reduction in film strength caused by the desizing process and ensure high heat resistance and low thermal expansion, the multilayer polyimide film according to the first embodiment preferably satisfies condition 1 below, more preferably condition 2 below, and even more preferably condition 3 below. Furthermore, to adjust the coefficient of linear expansion of the film to an appropriate range and effectively suppress the reduction in film strength caused by the desizing process, and to obtain a multilayer polyimide film that ensures high heat resistance, the multilayer polyimide film according to the first embodiment preferably satisfies condition 4 below.
[0089] Condition 1: The content of BPDI residues in the non-thermoplastic polyimide is more than 30 mol% and less than 70 mol% relative to all diamine residues constituting the non-thermoplastic polyimide, and the content of BENDA residues in the non-thermoplastic polyimide is more than 30 mol% and less than 70 mol% relative to all tetracarboxylic dianhydride residues constituting the non-thermoplastic polyimide.
[0090] Condition 2: The above condition 1 is satisfied, and the non-thermoplastic polyimide also has PDA residues as diamine residues.
[0091] Condition 3: The above condition 2 is satisfied, and the non-thermoplastic polyimide also has PMDA residues as acid dianhydride residues.
[0092] Condition 4: The above condition 3 is satisfied, and the non-thermoplastic polyimide also has ODA residues as diamine residues.
[0093] <Second Embodiment: Metal-Clad Laminate>
[0094] Next, the metal-clad laminate according to the second embodiment of the present invention will be described. The metal-clad laminate according to the second embodiment of the present invention is a metal-clad laminate obtained using the multilayer polyimide film according to the first embodiment of the present invention described above. In the following description, content that is repeated in the first embodiment will sometimes be omitted.
[0095] The metal-clad laminate according to the second embodiment has a multilayer polyimide film and a metal layer according to the first embodiment, wherein the metal layer is disposed on the main surface of at least one thermoplastic polyimide layer of the multilayer polyimide film. According to the second embodiment, since it has the multilayer polyimide film according to the first embodiment, the occurrence of defects (cracks, fractures, etc.) in the substrate (multilayer polyimide film) can be suppressed during the FPC manufacturing process. Hereinafter, an example of the metal-clad laminate according to the second embodiment will be described with reference to... Figure 2 The explanation will be provided later. Figure 2 This is a cross-sectional view illustrating an example of the metal-clad laminate according to the second embodiment.
[0096] like Figure 2 As shown, the metal-clad laminate 20 has a multilayer polyimide film 10 and a metal layer 13, the metal layer 13 being disposed on the main surface 12a of at least one thermoplastic polyimide layer 12 of the multilayer polyimide film 10.
[0097] Metal foil can be used as the metal layer 13. There are no particular limitations on the metal foil used; any metal foil can be used. For example, metal foils made of copper, stainless steel, nickel, aluminum, and alloys of these metals are suitable. Furthermore, in conventional metal-clad laminates, rolled copper foil, electrolytic copper foil, and other copper foils are mostly used, and copper foil is also preferred in the second embodiment.
[0098] Furthermore, the metal foil can be surface-treated to adjust its surface roughness, etc., according to its intended purpose. Furthermore, a rust-preventive layer, a heat-resistant layer, an adhesive layer, etc., can be formed on the surface of the metal foil. The thickness of the metal layer 13 is not particularly limited; it can be a thickness sufficient to perform its intended function, depending on the application. To suppress wrinkles during lamination with the multilayer polyimide film 10 and to facilitate the thinning of the FPC, the thickness of the metal layer 13 is preferably 5 μm or more and 50 μm or less.
[0099] When manufacturing a metal-clad laminate 20 using a multilayer polyimide film 10, a metal foil that forms the metal layer 13 is bonded to at least one side of the multilayer polyimide film 10 (e.g., Figure 2 In the case of the thermoplastic polyimide layer 12, the main surface 12a is the thermoplastic polyimide layer 12. There are no particular limitations on the method for bonding the metal foil to the main surface 12a of the thermoplastic polyimide layer 12, and various known methods can be used. For example, a continuous processing method based on a hot roll lamination apparatus with one or more metal rolls or a double steel belt press (DBP) can be used. The specific configuration of the means for performing hot roll lamination is not particularly limited, but to ensure a good appearance of the resulting metal-coated laminate 20, it is preferable to place a protective material between the pressure surface and the metal foil.
[0100] When thermoplastic polyimide layers 12 are provided on both sides of the non-thermoplastic polyimide layer 11, a double-sided metal-coated laminate (not shown) is obtained by bonding metal foil to both sides of the multilayer polyimide film 10.
[0101] When manufacturing FPC using metal-clad laminate 20, the FPC yield can be improved even when using a roll-to-roll method. That is, even when using a roll-to-roll method for descaling, the reduction in strength of the multilayer polyimide film 10 in the metal-clad laminate 20 is suppressed. Therefore, during the FPC manufacturing process, the occurrence of defects in the substrate (multilayer polyimide film 10) can be suppressed. As a descaling method, known methods can be used. For example, a wet descaling method including the following steps can be employed: a swelling step using an alkaline aqueous solution or a solution containing an organic solvent; a roughening step using an alkaline aqueous solution containing sodium permanganate, potassium permanganate, etc.; and a neutralization step.
[0102] <Method for manufacturing multilayer polyimide films>
[0103] Next, an example of a method for manufacturing a multilayer polyimide film according to the first embodiment will be described.
[0104] [Manufacturing method of polyamic acid]
[0105] The production method (synthetic method) of polyamic acid, a precursor of polyimide, can utilize all known methods and combinations thereof. A characteristic of the polymerization method in the production of polyamic acid lies in the order of monomer addition; by controlling this order, the various physical properties of the resulting polyimide can be controlled. In the case of synthesizing polyamic acid from diamines and tetracarboxylic dianhydrides, the desired polyamic acid (polymer of diamine and tetracarboxylic dianhydride) can be obtained by adjusting the amount of diamine (or the amount of each diamine when using multiple diamines) and the amount of tetracarboxylic dianhydride (or the amount of each tetracarboxylic dianhydride when using multiple tetracarboxylic dianhydrides). The molar fraction of each residue in the polyimide formed from polyamic acid is, for example, consistent with the molar fraction of each monomer (diamine and tetracarboxylic dianhydride) used in the synthesis of polyamic acid. The temperature conditions for the reaction of the diamine with tetracarboxylic dianhydride, i.e., the synthesis reaction of polyamic acid, are not particularly limited, but are, for example, in the range of 10°C or higher and 150°C or lower. The reaction time for the synthesis of polyamic acid is, for example, in the range of 10 minutes to 30 hours. Any monomer addition method can be used in the manufacture of polyamic acid. Representative methods for manufacturing polyamic acid include the following.
[0106] As a method for manufacturing polyamic acid, for example, a method of polymerization by means of the following steps (Aa) and steps (Ab) (hereinafter, sometimes referred to as "A polymerization method").
[0107] (Aa): The process of reacting an aromatic diamine with an aromatic acid dianhydride in an organic solvent under an excess of aromatic diamine to obtain a prepolymer with amino groups at both ends.
[0108] (Ab): A process in which an aromatic diamine with a structure different from that used in step (Aa) is added, such that the aromatic diamines and aromatic acid dianhydrides in all steps are substantially equimolar, and an aromatic acid dianhydride with a structure different from that used in step (Aa) is further added and polymerized.
[0109] In addition, as a method for manufacturing polyamic acid, a method of polymerization by means of the following steps (Ba) and (Bb) can also be cited (hereinafter, sometimes referred to as "B polymerization method").
[0110] (Ba): A process in which an aromatic diamine and an aromatic acid dianhydride are reacted in an organic solvent under an excess of aromatic acid dianhydride to obtain a prepolymer with anhydride groups at both ends.
[0111] (Bb): A process in which an aromatic diamine with a structure different from that used in step (Ba) is added, such that the aromatic diamine and aromatic diamine in all steps are substantially equimolar, and then an aromatic diamine with a structure different from that used in step (Ba) is further added and polymerized.
[0112] In this specification, polymerization methods that specify the order of addition of diamines or dianhydrides to selectively react with any or specific diamines or dianhydrides (e.g., polymerization methods A and B described above) are referred to as sequential polymerization. Polymers obtained through sequential polymerization that have two types of chain segments are called diblock copolymers, and polymers that have three types of chain segments are called triblock copolymers. In contrast, in this specification, polymerization methods that do not specify the order of addition of diamines and dianhydrides (polymerization methods in which monomers react arbitrarily with each other) are referred to as random polymerization. Polymers obtained through random polymerization are called random copolymers.
[0113] As a polymerization method for obtaining polyimide that can further suppress the reduction in film strength caused by degumming treatment, sequential polymerization is preferred.
[0114] The weight-average molecular weight of the polyamic acid obtained by the above polymerization method is preferably in the range of 10,000 or more and 1,000,000 or less, more preferably in the range of 20,000 or more and 500,000 or less, and even more preferably in the range of 30,000 or more and 200,000 or less. If the weight-average molecular weight is 10,000 or more, it becomes easier for the polyamic acid to form a coating film. On the other hand, if the weight-average molecular weight is 1,000,000 or less, it exhibits sufficient solubility in solvents, and therefore, a coating film with a smooth surface and uniform thickness is obtained using the polyamic acid solution described later. The weight-average molecular weight used here refers to the polyethylene oxide equivalent value measured by gel permeation chromatography (GPC).
[0115] Polyimide can also be obtained by using a polyamic acid solution containing polyamic acid and an organic solvent. Organic solvents that can be used in polyamic acid solutions include, for example, urea solvents such as tetramethylurea and N,N-dimethylethylurea; sulfoxide solvents such as dimethyl sulfoxide; sulfone solvents such as diphenyl sulfone and tetramethyl sulfone; amide solvents such as N,N-dimethylacetamide, N,N-dimethylformamide (hereinafter sometimes referred to as "DMF"), N,N-diethylacetamide, N-methyl-2-pyrrolidone, and hexamethylphosphoric triamine; ester solvents such as γ-butyrolactone; haloalkanes such as chloroform and dichloromethane; aromatic hydrocarbon solvents such as benzene and toluene; phenolic solvents such as phenol and cresol; ketone solvents such as cyclopentanone; and ether solvents such as tetrahydrofuran, 1,3-dioxolane, 1,4-dioxane, dimethyl ether, diethyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, and p-cresol methyl ether. These solvents are usually used alone, but two or more can be appropriately combined as needed. When polyamic acid is obtained using the polymerization method described above, the reaction solution (the solution after the reaction) itself can be used as the polyamic acid solution for obtaining polyimide. In this case, the organic solvent in the polyamic acid solution is the same organic solvent used in the reaction during the polymerization method described above. Alternatively, a polyamic acid solution can be prepared by dissolving the solid polyamic acid obtained by removing the solvent from the reaction solution in an organic solvent.
[0116] Additives such as dyes, surfactants, leveling agents, plasticizers, silicones, and sensitizers can also be added to the polyamic acid solution. Furthermore, fillers can be added to the polyamic acid solution to improve various properties of the film, such as slip properties, thermal conductivity, electrical conductivity, corona resistance, and loop stiffness. Any filler can be used, but preferred examples include fillers formed from silica, titanium dioxide, alumina, silicon nitride, boron nitride, dicalcium phosphate, calcium phosphate, and mica.
[0117] The concentration of polyamic acid in the polyamic acid solution is not particularly limited, but is preferably 5% by weight or more and 35% by weight or less, and more than 8% by weight or less and 30% by weight or less, relative to the total amount of polyamic acid solution. When the concentration of polyamic acid is 5% by weight or more and 35% by weight or less, a suitable molecular weight and solution viscosity are obtained.
[0118] [Method for forming a non-thermoplastic polyimide layer]
[0119] There are no particular limitations on the method for forming a non-thermoplastic polyimide layer, and various known methods can be used. For example, a method for forming a non-thermoplastic polyimide layer (polyimide film) through the following steps i) to iv) can be cited.
[0120] Step i): In an organic solvent, an aromatic diamine is reacted with an aromatic tetracarboxylic acid dianhydride to obtain a polyamic acid solution (hereinafter sometimes referred to as "non-thermoplastic polyamic acid solution") containing a precursor of a non-thermoplastic polyimide.
[0121] Step ii): The step of coating a dopant solution containing the above-mentioned non-thermoplastic polyamic acid solution onto a support to form a coating film.
[0122] Step iii): The process of heating the above-mentioned coated film on a support to form a self-supporting polyamic acid film (hereinafter sometimes referred to as "gel film"), and then peeling the gel film off the support.
[0123] Step iv): Heating the above gel film to imidize the polyamic acid in the gel film and drying it to obtain a polyimide film containing non-thermoplastic polyimide (a polyimide film that becomes a non-thermoplastic polyimide layer in a multilayer polyimide film).
[0124] In step ii), there are no particular limitations on the method of coating the dopant onto the support. Methods using conventionally known coating devices such as die coaters, Comma coaters (registered trademarks), reverse coaters, and blade coaters can be employed.
[0125] Process ii) and subsequent processes are broadly classified into thermal imidization and chemical imidization. Thermal imidization involves coating a polyamic acid solution as a dopant onto a support and heating it to promote imidization without using dehydrating ring-closing agents or similar agents. Chemical imidization, on the other hand, uses a polyamic acid solution containing at least one of a dehydrating ring-closing agent and a catalyst as an imidization accelerator to promote imidization. Either method can be used, but chemical imidization offers superior productivity.
[0126] As a dehydrating ring-closing agent, acid anhydrides, represented by acetic anhydride, are suitable. As a catalyst, aliphatic tertiary amines, aromatic tertiary amines, heterocyclic tertiary amines, etc., are preferred, and isoquinoline is more preferred.
[0127] In step ii), a glass plate, aluminum foil, endless stainless belt, stainless steel drum, etc., are suitable as the support for coating the dopant solution. In step iii), heating conditions are set according to the thickness of the final film and the production speed. After partial imidization or drying, the film is peeled off from the support to obtain a polyamic acid film (gel film).
[0128] Next, in step iv), for example, the ends of the gel film are fixed to prevent shrinkage during curing while being heated to remove water, residual solvent, imidization accelerator, etc., from the gel film, so that the remaining polyamic acid is completely imidized, resulting in a polyimide film containing non-thermoplastic polyimide. The heating conditions can be appropriately set according to the thickness of the final film and the production speed.
[0129] [Method for forming the thermoplastic polyimide layer]
[0130] The thermoplastic polyimide layer is formed, for example, by coating at least one side of a polyimide film (non-thermoplastic polyimide layer) obtained from the above-mentioned non-thermoplastic polyamic acid solution with a polyamic acid solution containing polyamic acid as a precursor of thermoplastic polyimide (hereinafter, sometimes referred to as "thermoplastic polyamic acid solution"), followed by heating (drying and imidization of polyamic acid) to form the layer. According to this method, a multilayer polyimide film having a non-thermoplastic polyimide layer and a thermoplastic polyimide layer disposed on at least one side of the non-thermoplastic polyimide layer is obtained. Alternatively, a solution containing thermoplastic polyimide (thermoplastic polyimide solution) may be used instead of the thermoplastic polyamic acid solution to form a coating film containing a thermoplastic polyimide solution on at least one side of the non-thermoplastic polyimide layer, and the coating film may be dried to form a thermoplastic polyimide layer.
[0131] Alternatively, for example, a co-extrusion die can be used to form a laminate on a support having a layer containing a layer of polyamic acid as a precursor of a non-thermoplastic polyimide and a layer containing a layer of polyamic acid as a precursor of a thermoplastic polyimide. The resulting laminate is then heated to simultaneously form a non-thermoplastic polyimide layer and a thermoplastic polyimide layer. Alternatively, a continuous coating (continuous casting) process can be used to form a laminate having a layer containing a layer of polyamic acid as a precursor of a non-thermoplastic polyimide and a layer containing a layer of polyamic acid as a precursor of a thermoplastic polyimide. The resulting laminate is then heated to simultaneously form a non-thermoplastic polyimide layer and a thermoplastic polyimide layer. In these methods, by using a metal foil as a support, a metal-coated laminate (a laminate of multiple polyimide films and metal foils) is obtained simultaneously with the completion of imidization. In the case of manufacturing multilayer polyimide films containing three or more polyimide layers, it is suitable to use methods that repeat the above-described coating and heating processes multiple times, or to form multiple coated films by co-extrusion or continuous coating (continuous casting) and then heat them at once. Various surface treatments such as corona treatment or plasma treatment can also be applied to the outermost surface of the multilayer polyimide film.
[0132] Example
[0133] The present invention will be specifically described below with reference to embodiments, but the present invention is not limited to these embodiments.
[0134] <Methods for Determining Physical Properties>
[0135] First, the method for determining the physical properties of polyimide films is explained.
[0136] [Tensive modulus, stress at 10% strain, and slope of the plastic deformation zone]
[0137] The tensile modulus of the polyimide film was measured using a precision universal testing machine (Shimadzu Corporation's "AUTOGRAPH AGS-J") according to ASTM D882. Furthermore, the stress at 10% strain was obtained from the tensile modulus measurement data. Additionally, the slope of the plastic deformation region was calculated from the tensile modulus measurement data using the formula described above. The conditions for measuring the tensile modulus are shown below.
[0138] Sample (polyimide film) width: 15mm
[0139] Grip spacing: 100mm
[0140] Stretching speed: 200mm / minute
[0141] Measurement environment: temperature 23℃ and humidity 55%RH
[0142] [Coefficient of linear expansion (CTE)]
[0143] Using a thermal analysis apparatus (Hitachi High-Tech Corporation "TMA / SS6100"), under a nitrogen atmosphere, a polyimide film was heated from -10°C to 300°C at a heating rate of 10°C / min, then cooled back to -10°C at a cooling rate of 40°C / min, and then further heated to 300°C at a heating rate of 10°C / min. The coefficient of linear expansion was determined from the strain from 50°C to 250°C during the second heating. The measurement conditions are shown below.
[0144] Sample (polyimide film) dimensions: 3mm width, 10mm length
[0145] Load: 1g (9.8mN)
[0146] [Resistance to adhesive residue remover]
[0147] (Conditions for handling adhesive residue)
[0148] The desizing treatment conditions used to evaluate the desizing solution resistance of polyimide films are shown in Table 1. It should be noted that the values in the "Concentration" column of Table 1 refer to the concentration in the treatment solution (aqueous solution). Furthermore, a water washing process was performed between the swelling and roughening processes, and between the roughening and neutralization processes. Additionally, a water washing and drying process were performed after the neutralization process. The chemical solutions used in the swelling and roughening processes were both manufactured by MacDermid Performance Solutions Japan KK. The chemical solution used in the neutralization process was manufactured by ROHM AND HAAS ELECTRONIC MATERIALS ASIA LIMITED.
[0149] [Table 1]
[0150]
[0151] (Determination of fracture strain)
[0152] For polyimide films before degumming and polyimide films after degumming under the above conditions, the fracture strain (strain at fracture) was determined using a precision universal testing machine ("AUTOGRAPH AGS-J" manufactured by Shimadzu Corporation) according to ASTM D882 under the following conditions.
[0153] The shape of the sample used for testing: a dumbbell shape (size 6).
[0154] Width of the measurement site on the sample: 4mm
[0155] Grip spacing: 25mm
[0156] Stretching speed: 25mm / minute
[0157] Measurement environment: temperature 23℃ and humidity 55%RH
[0158] Next, the strain retention rate (in %) is calculated using the formula: "Strain retention rate = 100 × (Tear of the polyimide film after desizing treatment) / (Tear of the polyimide film before desizing treatment)". Then, a strain retention rate of 80% or higher is classified as "A", a strain retention rate of 50% or higher but lower than 80% is classified as "B", and a strain retention rate lower than 50% is classified as "C". If the result is A, it is evaluated as "The reduction in film strength caused by desizing treatment can be suppressed". On the other hand, if the result is B or C, it is evaluated as "The reduction in film strength caused by desizing treatment cannot be suppressed".
[0159] [Peel strength]
[0160] Electrolytic copper foil (3EC-M3S-HTE) with a thickness of 12 μm is deposited on both sides of a multilayer polyimide film. A protective film (Apical125NPI, thickness: 125 μm) is further deposited on the outer surface of each electrolytic copper foil. The film is then laminated under these conditions at a lamination temperature of 360°C, a lamination pressure of 307.7 N / cm, and a lamination speed of 1.0 m / min to obtain a flexible copper clad laminate (FCCL).
[0161] Then, according to JIS C6471-1995, using a tensile testing machine (Toyo Seiki Co., Ltd. "StrographVES1D"), at a temperature of 23°C and a humidity of 55% RH, at a tensile speed of 50 mm / min and a peel angle of 90°, the average peel strength when peeling 30 mm of the electrolytic copper foil (width: 1 mm) on one side of FCCL was taken as the peel strength. For any of Examples 1 to 6 and Comparative Examples 1 to 5 described later, the peel strength was 12 N / cm or higher.
[0162] <Preparation of polyamic acid solution>
[0163] The preparation methods of solutions P1 to P11 as non-thermoplastic polyamic acid solutions and solution P12 as thermoplastic polyamic acid solutions will be described below. It should be noted that the preparation of solutions P1 to P12 was carried out under a nitrogen atmosphere at a temperature of 20°C. Furthermore, the compounds and reagents will be referred to by the following abbreviations.
[0164] DMF: N,N-dimethylformamide
[0165] PDA: p-phenylenediamine
[0166] ODA: 4,4'-Diaminodiphenyl ether
[0167] m-TB: 4,4'-diamino-2,2'-dimethylbiphenyl
[0168] BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane
[0169] PMDA: Pyromellitic dianhydride
[0170] BPDA: 3,3',4,4'-Biphenyltetracarboxylic acid dianhydride
[0171] BTDA: 3,3',4,4'-benzophenone tetracarboxylic dianhydride
[0172] AA: Acetic anhydride
[0173] IQ: Isoquinoline
[0174] [Preparation of solution P1]
[0175] In a 2L glass flask, 328.91g of DMF, 11.85g of ODA, and 11.17g of m-TB were added. While stirring the contents of the flask, 19.07g of BTDA was slowly added. After visually confirming that the BTDA had dissolved, 9.04g of PMDA was slowly added while stirring the contents of the flask. After visually confirming that the PMDA had dissolved, the contents of the flask were stirred for another 30 minutes. Next, while stirring the contents of the flask, 2.13g of PDA was added, followed by 5.88g of PMDA, and the contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 0.86g, PMDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in the viscosity of the contents over a specified time. Then, when the viscosity of the contents of the flask reaches 2000 poise at a temperature of 23°C, the addition of PMDA solution and the stirring of the contents of the flask are stopped, resulting in solution P1 as a non-thermoplastic polyamic acid solution.
[0176] [Preparation of solution P2]
[0177] In a 2L glass flask, 328.94g of DMF, 9.19g of ODA, and 13.92g of m-TB were added. While stirring the contents of the flask, 19.02g of BTDA was slowly added. After visually confirming that the BTDA had dissolved, 9.01g of PMDA was slowly added while stirring the contents of the flask. After visually confirming that the PMDA had dissolved, the contents of the flask were stirred for another 30 minutes. Next, while stirring the contents of the flask, 2.13g of PDA was added, followed by 5.87g of PMDA, and the contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 0.86g, PMDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in the viscosity of the contents over a specified time. Then, when the viscosity of the contents of the flask reaches 2000 poise at a temperature of 23°C, the addition of PMDA solution and the stirring of the contents of the flask are stopped, resulting in solution P2 as a non-thermoplastic polyamic acid solution.
[0178] [Preparation of solution P3]
[0179] In a 2L glass flask, 328.81g of DMF, 9.30g of ODA, and 12.68g of m-TB were added. While stirring the contents of the flask, 19.24g of BTDA was slowly added. After visually confirming that the BTDA had dissolved, 9.26g of PMDA was slowly added while stirring the contents of the flask. After visually confirming that the PMDA had dissolved, the contents of the flask were stirred for another 30 minutes. Next, while stirring the contents of the flask, 2.87g of PDA was added, followed by 5.79g of PMDA, and the contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 0.87g, PMDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in the viscosity of the contents over a specified time. Then, when the viscosity of the contents of the flask reaches 2000 poise at a temperature of 23°C, the addition of PMDA solution and the stirring of the contents of the flask are stopped, resulting in solution P3 as a non-thermoplastic polyamic acid solution.
[0180] [Preparation of solution P4]
[0181] In a 2L glass flask, 328.55g of DMF, 9.52g of ODA, and 11.53g of m-TB were added. While stirring the contents of the flask, 17.50g of BTDA was slowly added. After visually confirming that the BTDA had dissolved, 9.48g of PMDA was slowly added while stirring the contents of the flask. After visually confirming that the PMDA had dissolved, the contents of the flask were stirred for another 30 minutes. Next, while stirring the contents of the flask, 3.67g of PDA was added, followed by 7.41g of PMDA, and the contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 0.89g, PMDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in the viscosity of the contents over a specified time. Then, when the viscosity of the contents of the flask reaches 2000 poise at a temperature of 23°C, the addition of PMDA solution and the stirring of the contents of the flask are stopped, resulting in solution P4, which is a non-thermoplastic polyamic acid solution.
[0182] [Preparation of solution P5]
[0183] In a 2L glass flask, 326.01g of DMF and 23.83g of m-TB were added. While stirring the contents of the flask, 35.09g of BTDA was slowly added. After visually confirming the dissolution of BTDA, the contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared BTDA solution (solvent: DMF, BTDA concentration: 1.09g, BTDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in viscosity over a specified time. Then, when the viscosity of the contents of the flask reached 2000 poise at 23°C, the addition of BTDA solution and stirring of the contents of the flask were stopped, yielding solution P5 as a non-thermoplastic polyamic acid solution.
[0184] [Preparation of solution P6]
[0185] In a 2L glass flask, 327.98g of DMF, 9.99g of ODA, and 9.08g of m-TB were added. While stirring the contents of the flask, 13.78g of BTDA was slowly added. After visually confirming that the BTDA had dissolved, 8.86g of PMDA was slowly added while stirring the contents of the flask. After visually confirming that the PMDA had dissolved, the contents of the flask were stirred for another 30 minutes. Next, while stirring the contents of the flask, 5.39g of PDA was added, followed by 11.97g of PMDA, and the contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 0.93g, PMDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in the viscosity of the contents over a specified time. Then, when the viscosity of the contents of the flask reaches 2000 poise at a temperature of 23°C, the addition of PMDA solution and the stirring of the contents of the flask are stopped, resulting in solution P6, which is a non-thermoplastic polyamic acid solution.
[0186] [Preparation of solution P7]
[0187] In a 2L glass flask, 328.14g of DMF, 8.45g of ODA, and 7.46g of m-TB were added. While stirring the contents of the flask, 20.39g of BTDA was slowly added. After visually confirming that the BTDA had dissolved, 1.38g of PMDA was slowly added while stirring the contents of the flask. After visually confirming that the PMDA had dissolved, the contents of the flask were stirred for another 30 minutes. Next, while stirring the contents of the flask, 6.84g of PDA was added, followed by 14.57g of PMDA, and the contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 0.92g, PMDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in the viscosity of the contents over a specified time. Then, when the viscosity of the contents of the flask reaches 2000 poise at a temperature of 23°C, the addition of PMDA solution and stirring of the contents of the flask are stopped, resulting in solution P7, which is a non-thermoplastic polyamic acid solution.
[0188] [Preparation of Solution P8]
[0189] In a 2L glass flask, 328.91g of DMF, 5.27g of ODA, and 16.20g of BAPP were added. While stirring the contents of the flask, 8.48g of BTDA was slowly added. After visually confirming that the BTDA had dissolved, 7.17g of PMDA was slowly added while stirring the contents of the flask. After visually confirming that the PMDA had dissolved, the contents of the flask were stirred for another 30 minutes. Next, while stirring the contents of the flask, 7.11g of PDA was added, followed by 14.92g of PMDA, and the contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 0.86g, PMDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in the viscosity of the contents over a specified time. Then, when the viscosity of the contents of the flask reaches 2000 poise at a temperature of 23°C, the addition of PMDA solution and the stirring of the contents of the flask are stopped, resulting in solution P8, which is a non-thermoplastic polyamic acid solution.
[0190] [Preparation of Solution P9]
[0191] In a 2L glass flask, 328.53g of DMF and 17.70g of ODA were added. While stirring the contents of the flask, 18.01g of BPDA was slowly added. After visually confirming the dissolution of BPDA, 4.00g of PMDA was slowly added while stirring the contents of the flask. After visually confirming the dissolution of PMDA, the contents of the flask were stirred for another 30 minutes. Next, while stirring the contents of the flask, 5.77g of m-TB was added, followed by 2.21g of PDA, and then 11.42g of PMDA. The contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 0.89g, PMDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in the viscosity of the contents over a specified time. Then, when the viscosity of the contents of the flask reaches 2000 poise at a temperature of 23°C, the addition of PMDA solution and the stirring of the contents of the flask are stopped, resulting in solution P9 as a non-thermoplastic polyamic acid solution.
[0192] [Preparation of solution P10]
[0193] In a 2L glass flask, 328.64g of DMF and 17.53g of ODA were added. While stirring the contents, 11.89g of BPDA was slowly added. After visually confirming the BPDA had dissolved, 6.51g of BTDA was slowly added while stirring. After visually confirming the BTDA had dissolved, 11.31g of PMDA was slowly added while stirring. After visually confirming the PMDA had dissolved, the contents were stirred for another 30 minutes. Next, while stirring, 5.72g of m-TB was added, followed by 2.19g of PDA, and then 11.31g of PMDA. The contents were stirred for another 30 minutes. Next, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 0.88 g, PMDA concentration: 7.2 wt%) was continuously added to the flask at a rate that prevented a rapid increase in viscosity. Then, when the viscosity of the contents of the flask reached 2000 poise at a temperature of 23°C, the addition of the PMDA solution and the stirring of the contents of the flask were stopped, yielding solution P10 as a non-thermoplastic polyamic acid solution.
[0194] [Preparation of solution P11]
[0195] In a 2L glass flask, 328.85g of DMF and 17.21g of ODA were added. While stirring the contents of the flask, 19.17g of BTDA was slowly added. After visually confirming the dissolution of BTDA, 3.89g of PMDA was slowly added while stirring the contents of the flask. After visually confirming the dissolution of PMDA, the contents of the flask were stirred for another 30 minutes. Next, while stirring the contents of the flask, 5.61g of m-TB was added, followed by 2.14g of PDA, and then 11.10g of PMDA. The contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 0.87g, PMDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in the viscosity of the contents over a specified time. Then, when the viscosity of the contents of the flask reaches 2000 poise at a temperature of 23°C, the addition of PMDA solution and the stirring of the contents of the flask are stopped, resulting in solution P11, which is a non-thermoplastic polyamic acid solution.
[0196] [Preparation of solution P12]
[0197] In a 2L glass flask, 673.24g of DMF and 71.83g of BAPP were added. While stirring the contents of the flask, 7.72g of BPDA was slowly added. After visually confirming the dissolution of BPDA, 31.30g of PMDA was slowly added while stirring the contents of the flask. After visually confirming the dissolution of PMDA, the contents of the flask were stirred for another 30 minutes. Then, while stirring the contents of the flask, a pre-prepared PMDA solution (solvent: DMF, PMDA concentration: 1.15g, PMDA concentration: 7.2% by weight) was continuously added to the flask at a rate that prevented a rapid increase in viscosity over a specified time. Then, when the viscosity of the contents of the flask reached 300 poise at 23°C, the addition of PMDA solution and stirring of the contents of the flask were stopped, yielding solution P12 as a thermoplastic polyamic acid solution.
[0198] For solutions P1 to P12, the diamines used and their proportions, as well as the dianhydrides used and their proportions, are shown in Table 2. It should be noted that in Table 2, "-" indicates that the component was not used. Furthermore, the values in the "Diamine" column of Table 2 represent the content of each diamine relative to the total amount of diamines used (100 mol%) (unit: mol%). Similarly, the values in the "Dianhydride" column of Table 2 represent the content of each dianhydride relative to the total amount of dianhydrides used (100 mol%) (unit: mol%). Additionally, for solutions P1 to P12, the molar fraction of each residue of polyamic acid in the prepared polyamic acid solutions is consistent with the molar fraction of each monomer (diamine and tetracarboxylic dianhydride) used in the synthesis of polyamic acid.
[0199] [Table 2]
[0200]
[0201] <Fabrication of Polyimide Film>
[0202] The following describes the methods for producing the polyimide films (specifically, non-thermoplastic polyimide films and multilayer polyimide films) of Examples 1-6 and Comparative Examples 1-5.
[0203] [Example 1]
[0204] (Preparation of non-thermoplastic polyimide film)
[0205] In a solution P1 containing 60.0 g of solution, 24.0 g of an imidization accelerator containing AA / IQ / DMF (weight ratio: AA / IQ / DMF = 8.06 / 3.77 / 12.17) was added to prepare a doped solution. Next, under an atmosphere below 0°C, the doped solution was degassed while stirring, and then coated onto an aluminum foil using a comma coater to form a coated film. The coated film was then heated at 110°C for 150 seconds to obtain a self-supporting gel film. The obtained gel film was peeled off from the aluminum foil, fixed to a metal frame, and heated at 250°C for 17 seconds, followed by heating at 350°C for 70 seconds for drying and imidization, resulting in a non-thermoplastic polyimide film with a thickness of 17.0 μm (the non-thermoplastic polyimide film of Example 1).
[0206] (Fabrication of multilayer polyimide films)
[0207] To a 60.0 g solution P1, 24.0 g of an imidization accelerator containing AA / IQ / DMF (weight ratio: AA / IQ / DMF = 8.06 / 3.77 / 12.17) was added to prepare a dopant solution (hereinafter referred to as "dopant solution D1"). Next, under an atmosphere below 0°C, dopant solution D1 was degassed while being stirred. Then, using a comma coater, each solution was coated onto an aluminum foil in the order of solution P12 / dopant solution D1 / solution P12 to form a three-layer coated film. The coated film was then heated at 120°C for 200 seconds to obtain a self-supporting gel film. The obtained gel film was peeled off from the aluminum foil, fixed to a metal frame, heated at 250°C for 17 seconds, and then heated at 350°C for 70 seconds for drying and imidization, to obtain a multilayer polyimide film with a three-layer structure of thermoplastic polyimide layer (thickness 4.0 μm) / non-thermoplastic polyimide layer (thickness 17.0 μm) / thermoplastic polyimide layer (thickness 4.0 μm) (multilayer polyimide film of Example 1).
[0208] [Examples 2-6 and Comparative Examples 1-5]
[0209] The types of solutions (non-thermoplastic polyamic acid solutions) are shown in Table 3. Except for this, polyimide films (specifically, non-thermoplastic polyimide films and multilayer polyimide films) of Examples 2-6 and Comparative Examples 1-5 were obtained using the same method as in Example 1. It should be noted that for any of Examples 2-6 and Comparative Examples 1-5, the amount of non-thermoplastic polyamic acid solution used in preparing the non-thermoplastic polyimide film and the multilayer polyimide film was 60.0 g.
[0210] <Results>
[0211] For Examples 1-6 and Comparative Examples 1-5, the types of solutions (non-thermoplastic polyamic acid solutions) used, the physical properties of the non-thermoplastic polyimide film, and the evaluation results of the desizing residue resistance of the multilayer polyimide film are shown in Table 3.
[0212] [Table 3]
[0213]
[0214] In the multilayer polyimide films of Examples 1-6, the non-thermoplastic polyimide layer contains a BTDA residue as a type of BENDA residue and an m-TB residue as a type of BPDI residue. In the non-thermoplastic polyimide layers of Examples 1-6, the content of BPDI residues is 30 mol% to 100 mol% relative to all diamine residues constituting the non-thermoplastic polyimide layer. It should be noted that the non-thermoplastic polyimide contained in the non-thermoplastic polyimide layers of Examples 1-6 is a block copolymer having specific chain segments.
[0215] As shown in Table 3, the evaluation result of the desizing sludge resistance of the multilayer polyimide films in Examples 1-6 is A. Therefore, the multilayer polyimide films of Examples 1-6 can suppress the reduction in film strength caused by desizing sludge treatment.
[0216] In the multilayer polyimide film of Comparative Example 1, the non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer does not contain BPDI residues. In the multilayer polyimide film of Comparative Example 2, the non-thermoplastic polyimide contained in the non-thermoplastic polyimide layer does not contain BENDA residues. In the non-thermoplastic polyimide layers of Comparative Examples 2-5, the content of BPDI residues is less than 30 mol% relative to all diamine residues constituting the non-thermoplastic polyimide layer.
[0217] As shown in Table 3, the evaluation results of the desizing sludge resistance of the multilayer polyimide films in Comparative Examples 1 to 5 were B or C. Therefore, the multilayer polyimide films of Comparative Examples 1 to 5 were unable to suppress the reduction in film strength caused by the desizing sludge treatment.
[0218] The results above indicate that the multilayer polyimide film of this invention can suppress the reduction in film strength caused by desizing.
[0219] Explanation of reference numerals in the attached figures
[0220] 10: Multilayer polyimide film
[0221] 11: Non-thermoplastic polyimide layer
[0222] 12: Thermoplastic polyimide layer
[0223] 13: Metal layer
[0224] 20: Metal-clad laminate
Claims
1. A multilayer polyimide film having a non-thermoplastic polyimide layer and a thermoplastic polyimide layer disposed on at least one side of the non-thermoplastic polyimide layer, The non-thermoplastic polyimide layer contains a tetracarboxylic dianhydride residue comprising a benzophenone backbone as a tetracarboxylic dianhydride residue and a diamine residue comprising a biphenyl backbone as a diamine residue. The content of the diamine residues containing the biphenyl backbone is 30 mol% or more and 100 mol% or less relative to all the diamine residues constituting the non-thermoplastic polyimide.
2. The multilayer polyimide film according to claim 1, wherein, The content of the tetracarboxylic dianhydride residues containing the benzophenone backbone is more than 30 mol% and less than 100 mol% relative to all tetracarboxylic dianhydride residues constituting the non-thermoplastic polyimide.
3. The multilayer polyimide film according to claim 1, wherein, The strain retention rate of the non-thermoplastic polyimide layer after degumming treatment at a processing temperature of 70°C and a processing time of 5 minutes is over 80%.
4. The multilayer polyimide film according to claim 1, wherein, The tensile stress of the non-thermoplastic polyimide layer at 10% strain is above 220 MPa.
5. The multilayer polyimide film according to claim 1, wherein, The coefficient of linear expansion of the non-thermoplastic polyimide layer is above 5.0 ppm / K and below 19.0 ppm / K.
6. A metal-clad laminate having a multilayer polyimide film as described in claim 1 and a metal layer, the metal layer being disposed on the main surface of at least one thermoplastic polyimide layer of the multilayer polyimide film.
Citation Information
Patent Citations
Method for manufacturing polyimide metal laminate
JP2012186377A
Polyimide laminate film
JP2017177604A